Stem Cell Therapy in Patients with Heart Failure - Vrtovec, Bojan (The Methodist Hospital, Houston, Texas, 2013)
Heart failure results from injury to the myocardium from a variety of causes, including ischemic and nonischemic etiologies. Severe heart failure carries a 50% 5-year mortality rate and is responsible for more than one-third of cardiovascular deaths in the United States.1 Heart failure progression is accompanied by activation of neurohormonal and cytokine systems as well as a series of adaptive changes within the myocardium, collectively referred to as left ventricular remodelling. The unfavorable alterations may be categorized broadly into changes that occur in the cardiac myocytes and changes that occur in the volume and composition of the extracellular matrix.2 Since remodelling in heart failure is progressive and eventually becomes detrimental, the majority of treatment strategies are aimed at stopping or reversing this process. Although medical management, cardiac resychronization therapy, and long-term or destination mechanical circulatory support have been successful in this regard, a considerable number of patients still progress to end-stage heart failure with limited therapeutic options. For these patients, stem cell therapies are being investigated as a safe treatment strategy for decreasing cardiac remodelling on top of conventional medical and device treatment.